The Geology of the Eloise Copper-Gold, Deposit, NW Queensland, Australia - T. Baker (The Australasian Institute of Mining and Metallurgy, 1994)
The Eloise Cu-Au deposit is 60 km SE of Cloncurry in NW Queensland and has a current indicated reserve of 3.2 Mt @ 5.8 per cent Cu, 1.5gA Au and I9g/t Ag. It is hosted by metasediments and metabasic rocks that underwent amphibolite facies metamorphism at 550-600¦C and less than 3.5 kb. Peak metamorphism coincided with the regional D2 event which produced an S2 foliation with north-south strike and variable sub-vertical to steep east or west dip. The deposit is associated with several major shear zones parallel to the S2 foliation. The lodes form part of a large alteration system that is localised by the retrograde shear zones. Homblende-biotite-quartz with minor sulphides occur early in the alteration paragenesis which is overprinted by chlorite-muscovite-pyrrhotite-chalcopyrite ¦calcite+¦nagnetite. The later assemblage replaces the earlier Fe-K alteration as well as Fe-rich metamorphic assemblages such as homblende, biotite and staurolite indicating a post peak metamorphism timing for ore formation. Although replacive textures are the most common, the alteration can display open space infill and brecciation as well as durchbewegung and mylonite textures indicating that mineralisation occurred during ongoing ductile deformation. All these features are crosscut by a later brittle phase of calcite-chlorite-quartz¦pyrite alteration.